THE EFFECT OF CHAIR AEROBIC EXERCISE WITH FAMILY SUPPORT ON HEMOGLOBIN A1C AMONG PERSONS WITH TYPE 2 DIABETES - Changpean, Siraphop; Korakotkamchon, Bhonpimon; Chareonkul, Ratanakhorn; Jaisit, Jaruayporn; Keawwong, Rungthiwa; Aidee, Pattamapron (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2024)
The purpose of this quasi-experimental research was to examine the effect of chair aerobic exercise with a family support program on hemoglobin A1C among individuals with Type 2 Diabetes Mellitus (T2DM). The sample consisted of 54 individuals with type 2 diabetes who attended the diabetes clinic at Maesuai Hospital in Chiang Rai province. The sample was divided into two groups, with 27 individuals in each: the experimental group and the control group. The experimental group received chair aerobic exercise with family support, which included education, practice, and four home visits. The control group received usual care. The instruments used in this study were the chair aerobic exercise program with family support and a perceived family support assessment tool. The content validity index (CVI) of the assessment was .82, and its Cronbach’s alpha coefficient was .97. Data were analyzed using descriptive statistics and t-tests. The results revealed that the experimental group, which received the chair aerobic exercise program with family support, had a lower average of hemoglobin A1C after receiving the program compared to before, and showed a greater decrease in the average of hemoglobin A1C compared to the control group, who received usual nursing care, with statistical significance (p < .05). These findings suggest that chair aerobic exercise with family support could effectively help in controlling blood glucose levels in individuals with type 2 diabetes.